'Penal Drift' and the Voluntary Sector. Issue 3 (4th September 2019) - MAGUIRE, MIKE; WILLIAMS, KATE; CORCORAN, MARY
Abstract: This article explores the concept of 'penal drift' – the gradual adoption of criminal justice culture, language, and working practices – in voluntary sector organisations (VSOs) commissioned to deliver services to offenders. It identifies increases in coerced attendance, obligations to report non‐compliance, targets to reduce reoffending, and contracts to 'process' high caseloads, as factors behind such drift, which can jeopardise relationships with service users and the sector's traditional 'value‐driven' approach. It is concluded that most VSOs have so far managed to resist these threats and to balance contractual obligations with adherence to core values. However, this comes at a cost in staff time and energy and is difficult to sustain. There are concerns that the longer‐term effects may be quite damaging to the sector.